Different measures of fear of crime and survey measurement error - Hardyns, Wim (2010)
The measurement of fear of crime is acknowledged as a hot methodological issue. Many studies have focused on the cognitive and behavioural components of fear. The emotional affective component of fear of crime has been studied rather less, however. Traditional measures of fear of crime fail to address the complexity of this concept. Knowledge of prevalence, frequency and intensity of fear are largely absent in a quantitative design. Following an alternative question structure, previous research has shown that ‘old’-style questions overestimate the everyday experience of fear (see Farrall, 2004; Farrall and Gadd, 2004; Gray, Jackson and Farrall, 2008). Furthermore, gender differences in fear of crime seem to be influenced by socially desirable answers by men (Sutton and Farrall, 2005). In this paper, we study differences in outcomes when measuring fear of crime using ‘old’-style questions (’avoidance behaviour’) and an alternative question structure introduced by Stephen Farrall (three-part questions treating prevalence, frequency and intensity of fear). We conducted a survey (2008) in eighteen postal code areas and interviewed 750 key informants. Descriptive analyses by gender were conducted for both the traditional avoidance behaviour scale and the alternative question structure that measures the emotional affective component of fear of crime. Subsequently some correlational analyses were conducted to examine how different these fear of crime measures are from supposed covariates such as perceived sense of community, perceived disorder and previous victimisation. Furthermore, we assessed the effects of social desirability on measures of fear of crime components and on the gender-fear relationship in particular. In short, measuring the emotional affective component of fear with an alternative question structure presents a totally different picture than can be found by measuring the behavioural component of fear of crime with a traditional scale such as avoidance behaviour. Second, different measures of fear of crime are especially differentially related to previous victimisation. Third, we found rather surprising effects of social desirability on gender differences in fear of crime